Implementation of a Telerobotic System Based on the Kinect Sensor for the Inclusion of People with Physical Disabilities in the Industrial Sector - Kern-Molina, J (Institute of Electrical and Electronics Engineers Inc., 2019)
This article describes the design and implementation of a telerobotic system through the Kinect sensor for the inclusion of people with physical disabilities in the industrial environment. For the development of the system, a master slave architecture was used and the communication was made wirelessly using the HC-05 module that uses a Bluetooth v2.0 protocol, for the movement of the servomotors of the 4 OFD manipulator and Arduino board was used. The validation of the system was carried out by performing a manual and an automatic process by a group of people who manipulated the robot by hand gestures. © 2019 IEEE.
Keywords: Bluetooth; Kinect; Robot manipulator; Telerobotic